Hubungan Kekuatan Otot Tungkai dan Power Lengan dengan Kemampuan Undering Shoot - Achmad Farhan Hidayat; Siti Nurrochmah (Jurnal Sporta Saintika, 2025)
This study focuses on examining and determining whether there is a relationship between leg muscle strength and arm muscle explosive power on the under-ring shoot ability of female basketball extracurricular participants at SMPN 4 Malang. This study uses an explanatory descriptive approach. The study population consisted of 63 female students, and the sample size was 50 female students using the Stratified Purposive Systematic Proportional Random Sampling technique with a proportion of 80%. The instruments used during data collection included leg and dynamometer tests, two-hand medicine ball throws, and under-ring shoot tests. The results showed that all independent and dependent variables were normally distributed, homogeneous, and linear. The multiple correlation results showed that leg muscle strength and arm muscle explosive power simultaneously had a significant relationship with under ring shoot ability, with a correlation coefficient of 0.823 and a contribution of 67.7%. Thus, the final result of this study is that under-ring shoot ability has a strong and linear correlation with the combination of both physical conditions, namely leg muscle strength and arm muscle explosive power, when analyzed simultaneously. Translated with DeepL.com (free version).